COMPOSITION OF DEATH RISK ACCORDING TO BEHAVIORAL FACTORS (SMOKING, ALCOHOL CONSUMPTION) BY THE RESULTS OF 27-YEAR PROSPECTIVE STUDY - A. Yu. Ivanova; I. V. Dolgalev (Кардиоваскулярная терапия и профилактика)
Aim. To assess the all-cause and cardiovascular mortality by the results from prospective cohort study of non-organized inhabitants of Tomsk city depending on behavioral risk factors — smoking, alcohol consumption, in 25 years observation.Material and methods. The study was done on the model of nonorganized Tomsk city population. Totally, 1546 persons studied, of the age 20-59 y.o., 630 males, 916 females. The parameters of all-cause and cardiovascular mortality studied, as the prognostic significance of behavioral risk factors — smoking, alcohol consumption, in the all-cause mortality origin, as the mortality from cardiovascular diseases.Results. The data acquired, on the increase of all-cause mortality risk in smokers 2,34 times, 1,93 times in men and 1,99 in women. Among those having quit smoking, mortality risk was also higher comparing to nonsmokers — 1,86 in general population; 1,83 in men. Cardiovascular mortality risk is also significantly higher in those influenced by tobacco smoking: relative mortality risk 1,58, females — 1,93; no significant data for males. Relative risk increases in those consuming alcohol frequently, 2,55 times comparing to those non-drinking, especially in younger age strata. Gender analysis showed remaining of all relations for whole population in men, and in women there were significant results only for frequent alcohol intake.Conclusion. It was shown that smoking significantly increases the risk of all-cause mortality among persons of both ages; among those quit smoking risk of death is still higher as in current smokers, comparing to non-smokers. Frequent alcohol consumption increases the risk of alcohol intake 2.6 times comparing to non-drinkers. Moderate and rare alcohol intake also increases the risk of all-cause mortality.